An economic model of wineries and enotourism - Jason Winfree; Christopher S. McIntosh; Timothy Nadreau (Wine Economics and Policy, 2018)
This paper uses a theoretical model to analyze the interaction between general wine sales and enotourism since many wineries sell wine through wine tours as well as wine to non-tourists. We assume that consumers of wine tours, or enotourists, are wine connoisseurs whereas naive wine drinkers drive non-tourism sales. In our model, enotourists use wine tours to judge the quality of the wine, which forms a reputation that is then used by naive wine consumers. We show that wineries may want to decrease (increase) the price of wine via enotourism if their quality is higher (lower) than expected. We analyze this under both exogenous and endogenous quality. We also show that if wineries share a collective reputation, then minimum quality standards can benefit all wineries.
Keywords: 330; Collective reputation; Enotourism; Wine